Two new high altitude genera of Camiarini (Coleoptera: Leiodidae: Camiarinae) from Australia and New Zealand - Seago, Ainsley E.; Leschen, Richard A. B.; Newton, Alfred F. (Zootaxa, 2015)
Two new leiodid genera and species, Camisolus ptinoides gen. nov., sp. nov. and Camiarodes nunni gen. nov., sp. nov. are described from southeastern Australia and New Zealand, respectively. Each new species is placed within its own genus on the basis of morphological uniqueness within Camiarini (Camiarinae) based on the presence of an enlarged maxillary palpomere 4 and metanepisternum with a lateral, tongue-like process that overlaps the elytron in repose. A key to the described genera is provided for world Camiarini. The tribe, new to Australia, is otherwise known only from New Zealand (six genera including one new) and southern South America (one genus). Both new genera are found exclusively in high altitude areas.